Time - Agamben, Giorgio; Groom, Amelia (London : Whitechapel Gallery, 2013)
Marina Abramovic; Doug Aitken; Francis Alÿs; Matthew Buckingham; Janet Cardiff; Paul Chan; Moyra Davey; Dexter Sinister; Olafur Eliasson; Anthony gormley; Tehching Hsieh; Toril Johannessen; on Kawara; Joachim Koester; Lee Ufan; Christian Marclay; nova Milne; trevor Paglen; Philippe Parreno; Katie Paterson; Raqs Media Collective; Sylvia Sleigh; Simon Starling; Hito Steyerl; Hiroshi Sugimoto
Formerly CIP.
boek
Keywords: Time in art; Art, Modern